Theory of Connectivism in the Network Learning Process of Cell Respiration (Docentes 2.0 Journal, 2021)
The basic cycle of medicine programs comprises subjects characterized by being taught in a traditionalist way, presenting complex and constantly updated content, generating difficulties and rejection in the apprentices. For this reason, the present work aimed to analyze the incidence of George Siemens' connectivism in the network learning process in Biochemistry and Molecular Biology courses. This theory proposes tools to improve student learning through immersion, navigation, and construction of attractive, self-managed, and technology-mediated learning networks. Connectivism facilitated and motivated students to explore the tools they have at their disposal and are unknown to, invited them to build their learning network, and manage their training process. Qualitative research was carried out, based on the action research methodology, problem-based learning, and characteristics of connectivism, with undergraduate students of the first semester of Medicine. The population considered in this research were students from health careers who, within their training courses, had to take subjects related to biochemistry and molecular biology. Entry and exit questionnaires were applied, and interviews were used with the participants to design a didactic unit aimed at the construction of Blogs on cellular respiration, studied from various human physiological processes.
Keywords: Connectivism; Network Learning; Biochemistry; Molecular Biology